Meningkatkan Citra UKM Melalui Perancangan Ulang Identitas Visual - Lintang Widyokusumo (Humaniora, 2014)
The shift of economic trend into creative economy spurs Indonesia as a creative nation supported with cultural diversity, creative human resources and rich of natural resources to actively participate and contribute to the global economy. The power of Indonesian’s creative products is not inferior to other countries. However, the appeal of a product cannot be separated from the role of consistent and good visual identity design. Through this program Indonesian’s creative products will be more dignified, classy and echoed throughout the world.